1975
DOI: 10.1136/jnnp.38.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of L-dopa and 3-methoxydopa and improvement in clinical ratings and motor performance in patients with Parkinsonism treated with L-dopa alone or in combination with amantadine.

Abstract: SYNOPSIS Six patients with idiopathic Parkinsonism were treated with a combination of amantadine and L-dopa and after 12 to 24 weeks amantadine was replaced by placebo for a six week period in a double-blind trial. Although there was a tendency for clinical disability ratings and scores on objective ratings of motor skills to deteriorate initially after amantadine removal, there was no significant deterioration in clinical improvement or motor performance during the period of amantadine withdrawal. Amantadine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Hare et al (1973) found no correlation between peak plasma levels of levodopa and clinical response in 11 patients. Pilling et al (1975) likewise demonstrated no significant correlation between plasma levels and clinical improvement scores in 27 patients; However, they reported difficulty in 'obtaining plasma samples at a fixed time interval after the last dose of L-dopa'. Finally, Rinne et al (1973b) showed that clinical improvement during chronic levodopa administration was not correlated Significantly with total circulating levels or peak concentrations of levodopa in 173 patients.…”
Section: Studies That Fail To Find Correlation Between Plasma Dopa Comentioning
confidence: 86%
See 1 more Smart Citation
“…Hare et al (1973) found no correlation between peak plasma levels of levodopa and clinical response in 11 patients. Pilling et al (1975) likewise demonstrated no significant correlation between plasma levels and clinical improvement scores in 27 patients; However, they reported difficulty in 'obtaining plasma samples at a fixed time interval after the last dose of L-dopa'. Finally, Rinne et al (1973b) showed that clinical improvement during chronic levodopa administration was not correlated Significantly with total circulating levels or peak concentrations of levodopa in 173 patients.…”
Section: Studies That Fail To Find Correlation Between Plasma Dopa Comentioning
confidence: 86%
“…The difference in pyridoxine-induced levotration of levodopa achieved following oral dopa metabolism between parkinsonian patients administration (Rivera-Calimlim et aI., 1971; and normal control subjects may reflect an adapMearrick et aI., 1974). For example, in parkin-tive alteration in the decarboxylase system due to sonian patients with markedly slowed gastric chronic administration of levodopa (Mars, 1975). o~emptyffigYates~~levodopa'may~not provide~ade-~--This~alteI~tig!L@Y r~~ul!…”
Section: Gastro-intestinal Absorptionmentioning
confidence: 99%
“…This phenomenon does not appear to be as prevalent or as pronounced in patients taking levodopa concurrently (Fahn & Isgreen 1975). However, there are no known pharmacokinetic interactions between the two drugs (Pilling et al 1975). Amantadine can also alleviate the Parkinsonian side effects of the major tranquillisers (Greenblatt et al 1977).…”
Section: Drug Interactionsmentioning
confidence: 97%
“…In our patient group, no correlation was detected between the magnitude of the 2 h treatment effect and the corresponding difference in levodopa concentrations between active and placebo days, despite a more than thirteen fold variation between patients in the latter. Rinne et al (1973), Hare et al (1973 and Pilling et al (1975) were also unable to find any between patient relationship of plasma levodopa concentrations to response, and no therapeutic range has been established.…”
Section: Discussionmentioning
confidence: 99%